Peluang Dan Ancaman Perdagangan Produk Kerajinan Dan Kebijakan Untuk Mengatasinya : Studi Kasus Indonesia dengan Singapura - Anggun Restu Primurti; Daspar Daspar (Jurnal Ekonomi dan Bisnis Digital, 2025)
International trade plays a vital role in Indonesia's economic growth, with handicraft products being one of the promising sectors for development. This study explores the opportunities and threats in the trade of handicraft products between Indonesia and Singapore, and identifies policies that can enhance the competitiveness of Indonesian handicrafts in the international market. The research employs a literature review method by analyzing various sources, including official reports and academic journals. Findings indicate that Indonesia possesses advantages in cultural diversity, local raw materials, and skilled artisans. However, challenges remain, such as competitor product quality, price competition, trade regulations, and the dominance of foreign brands. Recommended strategies include improving product quality and innovation, adapting to market trends, collaborating with foreign distributors, and promoting cultural-based branding. With effective strategies, the handicraft trade between Indonesia and Singapore can be strengthened, generating economic benefits for both countries.